Tingkat Stres Mahasiswa Pada Pembelajaran Luring Masa Pandemi COVID-19 - Albinur Limbong; Idauli Simbolon (Jurnal Informasi dan Teknologi, 2022)
This research is a study of the stress level of students in offline learning at the beginning of the odd semester 2022/2023. Since the beginning of the COVID-19 pandemic, the learning model at the Indonesian Adventist University (UNAI) has changed from offline. Before the pandemic, online lectures were conducted (online) and later became hybrid learning (online and offline). After 1 year of the pandemic period, offline lectures will be implemented again starting in the 2022/2023 Odd Semester. This change in learning model has an impact on the stress level of students. The population data processed in this study were all students who took offline learning in the first month of the 2022/2023 Odd Semester, totaling 1,411 students. From the population, the test data was determined as many as 97 people who were chosen randomly. The test data has represented all students of each faculty, year of admission and gender. The results showed that the stress level of students in the low category. There is no significant difference in stress levels between the 6 faculties. Stress levels were also not significantly different between new and old students, between men and women, and between students who took a few courses and many. Academic and extracurricular programs conducted on campus and campus dormitories contribute to the low level of stress experienced by students at the beginning of the offline learning semester.